Doppler prediction of adverse perinatal outcome in intrauterine growth restriction - Mahale, Nina; Khanal, Bandana; Mahale, Ajit; Fernandes, Merwyn; Rao, Pallavi; Chavadi, Chanabasappa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Objective of current study was to determine and compare the diagnostic performance of Doppler ultrasonography of the fetal Middle Cerebral Artery (MCA) and Umbilical Artery (UA) for prediction of adverse perinatal outcome in suspected intrauterine growth restriction (IUGR). Methods: Fifty singleton pregnancies in third trimester of pregnancy with suspected intrauterine growth restriction were examined with Doppler ultrasonography of fetal MCA and UA. Results: Twenty patients of the fifty included patients had at least one major or minor adverse outcome. Major adverse outcome included perinatal deaths which included both intrauterine deaths and early neonatal deaths, hypoxic ischemic encephalopathy, intraventricular hemorrhage, periventricular leukomalacia, pulmonary hemorrhage, necrotizing enterocolitis and septicemia. Minor outcomes included cesarean section for fetal distress, Apgar score below 7 at 5 minutes and admission to Neonatal Intensive Care Unit (NICU) for treatment. MCA PI is the most sensitive(90%) index in predicting any adverse perinatal outcome i.e. including both major and minor outcomes, Positive Predictive Value (PPV) and specificity being greatest for MCA/UA PI (96.6%, 93.7%). For the major adverse outcome most sensitive (86.6%) most specific (91.4%) and with highest PPV (81.2%) and NPV (94.1%), is MCA/UA PI. Ratio of MCA/UAPI is more sensitive (90%) than PI of both the arteries alone for overall prediction of adverse perinatal outcome. Conclusions: Thus we conclude that the Doppler studies of the multiple vessels in the fetoplacental unit can help in the monitoring of the compromised fetus and can help us predicting neonatal morbidity. This may be helpful in determining the optimal time of deliveries in pregnancies complicated by IUGR.